Cryptocurrencies, Evolution of Means of Payments and Validity of Monetary Principles - Edoardo Beretta (Credit and Capital Markets – Kredit und Kapital, 2021)
The paper explores the role, evolution and ruling principles of the concept of "money" in the 21st Century. In this continuously evolving context, cryptocurrencies and Blockchain technology are widely considered the most relevant monetary innovations of the last decades. By means of a macro-founded logical-analytical approach combined with statistical evidence, the paper provides arguments: 1. dismissing the "innovation myth" behind cryptocurrencies because of de facto representing a comeback of the private issue of means of payments and, more problematically, seigniorage at its best; 2. confirming that crypto-tokens do not comply with basic, still ruling monetary principles; 3. suggesting that excess liquidity is already invested in crypto-markets (which are themselves "inflationary", namely not backed by real value (i.e. GDP). The concrete risk is, once again in economic history, represented by facing a financial bubble.
Keywords: E44; E51; E58; 330; cryptocurrencies; inflation; money; payment; systems